Mechanical properties of graphene oxide (GO)/epoxy composites - Abdullah S.I.; Ansari M.N.M. (Taylor and Francis Ltd., 2023)
In this study, the effects of graphene oxide (GO) on composites based on epoxy resin were analyzed. Different contents of GO (1.56vol.%) were added to epoxy resin. The GO/epoxy composite was prepared using the casting method and was prepared under room temperature. Mechanical tests results such as tensile test, impact test and hardness test show enhancements of the mechanical properties of the GO/epoxy composite. The experimental results clearly show an improvement in the Youngs modulus, tensile strength and hardness. The impact strength was seen to decrease, pointing to brittleness increase of the GO/epoxy composite. A microstructure analysis using Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) analysis was also performed, which showed how GO impeded the propagation of cracks in the composite. From the SEM images we observed the interface between the GO and the epoxy composite. As can be seen from this research, the GO/epoxy composites can be used for a large number of applications. The results of this research are a strong evidence for GO/epoxy composites being a potential candidate for use in a variety of industrial applications, especially for automobile parts, aircraft components, and electronic parts such as supercapacitors, transistors, etc. 2014 Housing and Building National Research Center. Production and hosting by Elsevier B.V.